Examining the Professional Excellence Programme: Inducting University Teachers into the Higher Education System in South Africa - Samson Matope; Zwelijongile Baleni (E-Journal of Humanities, Arts and Social Sciences, 2023)
The obligation to increase the standard of instruction and learning falls on academic developers. A crucial part of academic staff development at institutions of higher learning is the induction of academics who are primarily subject matter specialists without the pedagogical abilities to teach effectively in the higher education environment. This qualitative essay investigated how the Professional Excellence Programme (PEP) might be utilised as an induction Short Learning Programme (SLP) for new academics. After finishing the brief SLP, the inductees were given a questionnaire to evaluate the modules (Teaching and Learning, Curriculum Development, and Assessment in Higher Education) and qualitative data was gathered. The study was framed by Wegner’s social learning theory. The research showed that the PEP programme can be an efficient programme to develop academics into university teachers. Since the SLP was accepted by all participants in the study, the study recommended that the Directorate of Teaching and Learning should develop the PEP programme into a credit-bearing postgraduate diploma in higher education at NQF Level 8, which is equivalent to an honours degree.